PEDAMPINGAN PEMBUATAN MODUL BIMBINGAN DAN KONSELING KURIKULUM MERDEKA UNTUK GURU BK TINGKAT SMP DAN SEDERAJAT DI KABUPATEN MEMPAWAH - Hendrik; Hastiani; Martin; Atika, Amelia; Wahyu Hidayati, Novi (Jurnal Berdaya Mandiri, 2024)
The BK work program in schools is shown in physical form, namely the BK module which contains service plans according to student needs. The efforts made to carry out this role, guidance and counseling teachers are required to make a service implementation plan. The problem faced by guidance and counseling teachers in the current independent curriculum, is that their skills in compiling guidance and counseling modules are not yet optimal according to the context of the Pancasila student profile and the achievements of the independent curriculum. Therefore, assistance is needed for guidance and counseling teachers at junior high school and equivalent levels to prepare guidance and counseling modules. The subjects who attended the service activities consisted of 50 public and private middle school guidance and counseling teachers. This activity collaborates with the Mempawah Regency Guidance and Counseling Teachers' Conference (MGBK), located at 2 Junior High Schools Mempawah. The methods used identification, discussion and practicum in creating guidance and counseling service modules, evaluation and reflection. The results of implementing community service are providing skills in creating independent curriculum guidance and counseling service modules based on needs analysis according to development phases and creating service achievements based on Pancasila student profile indicators. Keywords: Assistance, Curriculum, Modules, Services,